L’anello che non tiene. Diagnosi, eziopatogenesi e terapia dell’attacco di panico - Sneider, Maria; Cecchitelli, Caterina; Masillo, Alice (Il sogno della farfalla, 2006)
The aim of this article is to take a deep look into a very widespread disorder, the panic attack. The quick outbreak of the showy symptomology in an apparent state of psychophysical well-being, raises many questions as to the causes of its onset. In order to carry out this research we started from a close examination of the theories of anxiety. The corroboration of the organicist approach which has conditioned all the psychiatric nosography up until today has led us to reformulate the diagnosis, the etiopathogenesis and the therapy of the panic attack in the light of M. Fagioli’s theory. As well as a clinical examination of the phenomenon we have looked for a connection between this mental pathology and the historical moment in which it emerges in a preponderant way. The psychopathologic examination leads us to discover that the panic attack is nothing other than the breakdown of a false equilibrium, based on the annulment of affects. When human relationships “reemerge” and are once again felt, the crisis occurs. During the course of the disorder the patient finds him/herself at a crossroad: either continue to lack affectivity and put up with the symptom, or give up the schizoid way of conducting relationships. In order to pursue the second way the therapist must not stop at simply curing the symptom but must bring the patient to recuperate his lost birth.